Contribution of External and Internal Phosphorus Sources to Grain P Loading in Durum Wheat (Triticum durum L.) Grown Under Contrasting P Levels - El Mazlouzi, Mohamed; Morel, Christian; Chesseron, Coralie; Robert, Thierry; Mollier, Alain (Frontiers in Plant Science, 2020)
Phosphorus (P) in durum wheat grains after anthesis originates from either the external P source or the internal remobilization of P from different plant organs. The supply of P and its use by the plant are important factors that can affect the contribution of each source to grain P nutrition. Thus, this experiment aimed to quantify the origin of P in grains of durum wheat plants with different P nutritional status. Wheat plants were grown from juvenile stages to maturity in complete nutrient solutions with either high (0.125 mM) or low (0.025 mM) P concentrations in greenhouse conditions. Phosphorus in nutrient solutions was spiked by introducing 32P after anthesis to quantify the external P uptake and its partitioning within plant organs (spikelets, leaves, stems, roots, and post-anthesis tillers) and grains. Phosphorus use efficiency in durum wheat plants was also determined. The low and high P supply resulted in two highly different plant nutritional P status. Plants with low P status remobilized most of their stored P in all organs and allocated more than 72% of post-anthesis P uptake to grain P nutrition, whereas in the high P plants this was only 56%. Enhanced remobilization of P and the efficient allocation of newly acquired P to grains were crucial for durum wheat grain P nutrition grown under low P supply. The remobilization of P represented 81% of grain P in low P plants while it represented 65% for high P plants. Organs that contributed the most to P remobilization in low P plants were spikelets (43%) and leaves (35%). The post-anthesis tiller development was reduced in low P plants suggesting a preferential allocation of P to grains under this treatment. We concluded that P loading into grains in durum wheat is mainly derived from the remobilization of internal P sources stored before anthesis, even at high external P supply during grain filling.